Field-induced phase transitions in an antiferroelectric liquid crystal using the pyroelectric effect. - VIJ, JAGDISH KUMAR (American Physical Society, 2000)
The antiferroelectric liquid crystal (AFLC) under investigation possesses different helical polar phases. Measurements of pyroelectric response of these phases as a function of temperature and bias field have elucidated the ability of this method for investigating the nature of antiferroelectric phases and phase transitions under the bias field. The pyroelectric signal as a function of the bias field at fixed temperatures and as a function of temperature for fixed bias fields was measured for different phases of the investigated AFLC material. A theoretical model describing the pyroelectric response in different phases of AFLC is given, and the experimental results are interpreted. The threshold fields for field induced phase transitions are determined. The type of field induced phase transition from the AF phase in particular is found to be dependent on the temperature within its range. The properties of an unusual ferrielectric phase existing between ferrielectric chiral smectic-C(SmC*) and antiferroelectric AF phases are studied in a great detail. The results confirm that this phase is one of the incommensurate phases, predicted by the axial next-nearest neighbor Ising model and Landau model for this temperature region.
PUBLISHED
Keywords: Condensed matter physics; antiferroelectric liquid crystal